1997
DOI: 10.1021/la960881g
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Adsorption Studies of Coated and Chemically Modified Chromatographic Silica Gels

Abstract: A series of physically coated and/or chemically bonded silica gel samples was characterized by means of nitrogen adsorption at 77 K in a relative pressure range from 10-6 to 0.99. The LiChrospher Si-100 chromatographic silica gel was modified by using 4‘-cyano-4-biphenyl [4-(4-pentenyloxy)]benzoate and 4-biphenyl [4-(4-pentenyloxy)]benzoate, whose contents in the samples varied from 8 to 46 wt %. Standard characterization methods were used to obtain the specific surface area (BET method), the micropore volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 13 publications
2
51
0
2
Order By: Relevance
“…1, 2; Table 1). Similar changes were observed in the case of the modification of silica gels by coal deposits [28,29], proteins [30], and organosilanes [31,32].…”
Section: Resultssupporting
confidence: 78%
“…1, 2; Table 1). Similar changes were observed in the case of the modification of silica gels by coal deposits [28,29], proteins [30], and organosilanes [31,32].…”
Section: Resultssupporting
confidence: 78%
“…Note that these samples did not possess micropores (pore size < 2 nm). In the case of the microporous silicas, the low-pressure adsorption behaviours could have been affected by the presence of micropores, with this effect becoming more pronounced with decreasing micropore size (Kruk et al 1997b). shows that the APD for the former exhibited several features reflecting monolayer formation, fluid-solid transition and multilayer formation, while the APD for the silica surface was a decreasing, rather featureless, function.…”
Section: Resultsmentioning
confidence: 88%
“…5 µm. This silica was modified with Kruk et al 1999c) and microporous carbon J (data reported by Kruk et al 1999b). The data points refer to the following samples: (a) ᭺, Carbopack F; , carbon J; (b) ᭺, Carbopack F; ᭹, carbon J.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermogravimetry, especially its high-resolution option, was also found to be useful for characterization of modified silica gels (17)(18)(19)(20)(21). Gas and vapor adsorption, especially nitrogen adsorption at 77 K, are the techniques of choice for studying not only the surface properties of siliceous adsorbents but also their porous structures (19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%